Radiocaesium accumulation and fluctuating asymmetry in the Japanese mitten crab, Eriocheir japonica, along a gradient of radionuclide contamination at Fukushima. (1st January 2022) - Fuller, Neil; Smith, Jim T.; Takase, Tsugiko; Ford, Alex T.; Wada, Toshihiro
Abstract: The 2011 Tohoku earthquake-tsunami and the subsequent nuclear accident at the Fukushima Dai-ichi Nuclear Power Station (FDNPS) led to large-scale radionuclide contamination of the marine and freshwater environment. Monitoring studies of marine food products in the Fukushima region have generally demonstrated a declining trend in radiocaesium concentrations. However, the accumulation and elimination of radiocaesium and potential biological effects remain poorly understood for freshwater biota inhabiting highly contaminated areas at Fukushima. Consequently, the present study aimed to assess radiocaesium accumulation and developmental effects on the commercially important catadromous Japanese mitten crab, Eriocheir japonica . E. japonica were collected from four sites along a gradient of radionuclide contamination 4–44 km in distance from the FDNPS in 2017. To determine potential developmental effects, fluctuating asymmetry (FA) was used as a measure of developmental stability. Combined 134 Cs and 137 Cs values for whole E. japonica from highly contaminated sites 4 and 16 km in distance from the FDNPS were 3040 ± 521 and 2250 ± 908 Bq kg −1 wet weight respectively, 30 and 22 times greater than the Japanese standard limit of 100 Bq kg −1 . Estimated total dose rates based on radiocaesium concentrations in whole crabs and sediment ranged from 0.016 to 37.7 μGy h −1 . No significant relationship between radiocaesium accumulation and FA was recorded, suggesting that chronic radiation exposure at Fukushima is not inducing developmental effects in E. japonica as measured using fluctuating asymmetry . Furthermore, estimated dose rates were below proposed regulatory limits where significant deleterious effects are expected. The present study will aid in the understanding of the long-term consequences of radiation exposure for non-human biota and the management of radioactively contaminated environments. Graphical abstract: Image 1 Highlights: Radiocaesium accumulation assessed in Eriocheir japonica at Fukushima. Estimated total dose rates for E. japonica ranged from 0.016 to 37.7 μGy h −1 Japanese standard limit for consumption exceeded at two sites by 22 and 30 times. Fluctuating asymmetry used as measure of developmental stability. No significant effect of radiation on developmental stability of E. japonica.